Gender gap in Slovakia: selected problems of education and career - Danielová, Katarína; Lauko, Viliam (Journal for Geography, 2016)
The article focuses on the gap between women education and their career. Women’s education has significantly increased in a few last years, but their position on the labour market has been more difficult in comparison with men. The share of economical active women and also the share of working women with higher education have been growing till the present time. However, it is questionable how do women use their higher education in career or whether they can build even some career. We have used the data from Statistical Office of the Slovak Republic and some problems have been presented in the area of Slovakia on the level of regions (kraje).
Keywords: gender gap; education; career; Slovakia; leaky pipeline